1995
DOI: 10.1021/bi00044a017
|View full text |Cite
|
Sign up to set email alerts
|

The B Form to Z Form Transition of Poly(dG-m5dC) Is Sensitive to Neutral Solutes Through an Osmotic Stress

Abstract: Several neutral solutes, ranging in size from methanol to a tetrasaccharide, stachyose, are shown to stabilize the left-handed Z form of the methylated polynucleotide poly(dG-m5dC). The action of these solutes is consistent with an osmotic stress, that is, with their effect on water chemical potentials coupled to a difference in the number of associated water molecules between the B and Z conformations. The apparent difference in hydration between the two forms is, however, dependent on the particular solute u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 32 publications
2
45
4
Order By: Relevance
“…By using two different model approaches, the Wyman linkage equation or the Gibbs Duhem equation, we found that 65-72 1 water molecules are linked to the binding of four oxygen molecules to human Hb under the experimental conditions used. Furthermore, this hydration change was found to be in agreement with the difference between the solvent-accessible surface areas of deoxy-and oxy-Hb computed from x-ray structures by Clothia et al (5,6).The experimental approach and analyses originally used by us to assess and quantify the role of water on the allosteric control of Hb have been tested in several other biochemical systems (7)(8)(9)(10)(11)(12)(13)(14). A standard linear dependence of equilibrium and kinetic free energy parameters on water activity rather than solute activity has been lately reported.…”
supporting
confidence: 74%
“…By using two different model approaches, the Wyman linkage equation or the Gibbs Duhem equation, we found that 65-72 1 water molecules are linked to the binding of four oxygen molecules to human Hb under the experimental conditions used. Furthermore, this hydration change was found to be in agreement with the difference between the solvent-accessible surface areas of deoxy-and oxy-Hb computed from x-ray structures by Clothia et al (5,6).The experimental approach and analyses originally used by us to assess and quantify the role of water on the allosteric control of Hb have been tested in several other biochemical systems (7)(8)(9)(10)(11)(12)(13)(14). A standard linear dependence of equilibrium and kinetic free energy parameters on water activity rather than solute activity has been lately reported.…”
supporting
confidence: 74%
“…The negative sign means that the nonspecific complex sequesters more water than the specific one. (18). The apparent Anw for sucrose, for example, is about 3-4 times larger than for glycerol.…”
Section: [4]mentioning
confidence: 94%
“…The macromolecular reactions we have studied that clearly involve a change in exposed surface area, as, for example, the BZ transition of poly(dG-m 5 dC) (16) and the binding of free E. coli gal repressor to its operator sequence (17), showed that the exclusion of each individual solute could be well described by a constant number of included waters, ⌬N ew ab , (over the range of solute concentrations used), but this difference in the excess number of waters between two states is very sensitive to both the size and chemical nature of the solute probing the reaction.…”
Section: Preferential Hydrationmentioning
confidence: 99%